Sustainability perspective to support decision making in structural retrofitting of buildings: a case study - Oliveira, Rui (2022)
The reuse of existing materials in buildings can give a contribution to sustainable practices such as a balance in embodied energy, water, and emission reduction. However, it is not always possible to maintain the existing structural materials because some different technical variables could hamper their usability, namely seismic reinforcement needs, fire safety protection, conservation state, and new legal requirements. The paper follows a case study approach for assessing the technical and environmental performances of structural options for old building retrofitting works. All structural options were analyzed through the results of several categories of environmental impact. Some parameters of a retrofitting management system were also used to frame in a comprehensive way the technical constraints pertaining to building retrofitting works. The structural option choice was taken by the owner with the contribution of the design team and the construction manager of the construction project as well as the results of interviews with other construction professionals, considering the variables related to technical suitability and environmental impact. The results of the study show that the steel structure is the solution that best addresses the technical constraints of the building retrofit works and minimizes environmental impact. The results of the study also suggest that the consideration of other variables other than the technical ones can contribute to the effective functioning of the renovation subsegment of the building market. Some suggestions for further studies to enhance the results of this work are put forward.